2020
DOI: 10.3390/jcm9030843
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antioxidative Defense by Vitamins C and E Consumption Prevents 7-Day High-Salt Diet-Induced Microvascular Endothelial Function Impairment in Young Healthy Individuals

Abstract: This study aimed to examine whether the oral supplementation of vitamins C and E during a seven-day high salt diet (HS; ~14 g salt/day) prevents microvascular endothelial function impairment and changes oxidative status caused by HS diet in 51 (26 women and 25 men) young healthy individuals. Laser Doppler flowmetry measurements demonstrated that skin post-occlusive reactive hyperemia (PORH), and acetylcholine-induced dilation (AChID) were significantly impaired in the HS group, but not in HS+C+E group, while s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 50 publications
8
45
0
Order By: Relevance
“…For instance, a high-sodium diet reduces the NO-mediated increase in skin blood flow in response to local heating in young, salt-resistant normotensive individuals [ 26 ]. In agreement with this finding, a high-sodium diet blunts the cutaneous blood flow response to ACh delivered via intradermal infusion [ 27 ] or iontophoresis [ 28 , 29 ]. Likewise, cutaneous post-occlusive reactive hyperemia is blunted in the absence of a change in BP following excess sodium consumption [ 28 , 30 ]; however, cutaneous reactive hyperemia appears to be mediated by endothelial release of prostaglandins rather than NO [ 30 , 31 ], and is beyond the scope of this review.…”
Section: Assessment Of Endothelial Functionmentioning
confidence: 65%
See 1 more Smart Citation
“…For instance, a high-sodium diet reduces the NO-mediated increase in skin blood flow in response to local heating in young, salt-resistant normotensive individuals [ 26 ]. In agreement with this finding, a high-sodium diet blunts the cutaneous blood flow response to ACh delivered via intradermal infusion [ 27 ] or iontophoresis [ 28 , 29 ]. Likewise, cutaneous post-occlusive reactive hyperemia is blunted in the absence of a change in BP following excess sodium consumption [ 28 , 30 ]; however, cutaneous reactive hyperemia appears to be mediated by endothelial release of prostaglandins rather than NO [ 30 , 31 ], and is beyond the scope of this review.…”
Section: Assessment Of Endothelial Functionmentioning
confidence: 65%
“…Likewise, Greaney et al demonstrated that local infusion of ascorbic acid restored the NO-mediated increase in skin blood flow to local heating in normotensive, salt-resistant individuals consuming excess sodium [ 26 ]. Oral supplementation with the antioxidant vitamins C and E during a high-sodium diet (5500 mg/day) similarly restored the skin blood flow response to cutaneous ACh iontophoresis while also preventing an increase in markers of oxidative stress in the plasma and urine [ 28 ].…”
Section: Mechanisms Contributing To Dietary Sodium-induced Impairmmentioning
confidence: 99%
“…LDF measurements were performed in a temperature-controlled room. General procedures for performing LDF PORH test and LDF iontophoresis of ACh and SNP tests were done in accordance with our well-established protocols, which are described in detail in previous papers of our research group [ 18 , 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…We have earlier reported that in normotensive salt-resistant individuals' microvascular reactivity in response to vascular occlusion following 7-day HS diet was strongly predicted by both antioxidant capacity and the level of the RAS activity, rather than antioxidant capacity alone [18]. These results potentiated the key role of normal RAS function in maintaining vascular homeostasis and indicated that the alteration in RAS during dietary salt perturbation could be involved in concomitant changes in endothelial function [18].…”
Section: Introductionmentioning
confidence: 91%
“…We have earlier reported that in normotensive salt-resistant individuals' microvascular reactivity in response to vascular occlusion following 7-day HS diet was strongly predicted by both antioxidant capacity and the level of the RAS activity, rather than antioxidant capacity alone [18]. These results potentiated the key role of normal RAS function in maintaining vascular homeostasis and indicated that the alteration in RAS during dietary salt perturbation could be involved in concomitant changes in endothelial function [18]. Since the SNS activity presents a significant regulator of the RAS activation, it became evident that in order to clarify the pathogenic relation between HS diet and impaired vascular function, it is necessary to investigate the effect of salt loading on major regulating systems, including RAS and autonomic nervous system (ANS) activity, in otherwise healthy individuals.…”
Section: Introductionmentioning
confidence: 94%